2020
DOI: 10.18178/ijesd.2020.11.4.1245
|View full text |Cite
|
Sign up to set email alerts
|

Tourist Behavior of Plastic Waste Reduction in the Coastal Area of Trang Province, Thailand

Abstract: The objective of this study is to estimate the tourist behavior of plastic waste reduction in the coastal area of Trang Province, Thailand. 316 tourists (153 male, 163 female) traveling in the five districts along with the coastal area were included as the participants in this study. The results showed that 57 % of the tourists were found to be good behavior. Amongst 14 variables in statistic analysis, knowledge was found as significant predictor after adjusting in full model of multiple logistic regression. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…It indicates that for every increase in behaviour score, the presence of plastic waste management will increase by 2.035 times compared to households who do not have behaviour. This result aligned with previous study done by [23].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…It indicates that for every increase in behaviour score, the presence of plastic waste management will increase by 2.035 times compared to households who do not have behaviour. This result aligned with previous study done by [23].…”
Section: Resultssupporting
confidence: 94%
“…There is a study showed that 80.2% of people who had a good knowledge would lead to a good behaviour while people who had a bad behaviour usually would have a poor knowledge on plastic waste, 58.4%. This shows that knowledge is very important in order for people to have good behaviour [23]. Many environmentalists believe that consumer ignorance was a main reason why some people do not recycle.…”
Section: Introductionmentioning
confidence: 99%
“…In the first instance, opportunities to reduce unnecessary use could be seized where this is feasible especially at shops like restaurants. In this case, policies should be incorporated to avoid disposable plastic items at restaurants and need to pay penalty in an offence [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…[39]. The amount of PW generated from the tourism sector depends on many factors, such as destination characteristics, accommodation type, travel mode, tourist behavior and attitudes, infrastructure, waste management systems, policy, and regulations [27,38,[40][41][42][43].…”
Section: B Impacts Of Plastic Waste On Tourismmentioning
confidence: 99%